Shaped-pulse optimization of coherent emission of high-harmonic soft X-rays - Kapteyn, H. C., author; Murnane, M. M., author; Christov, I. P., author; Vdovin, G., author; Misoguti, L., author; Zeek, E., author; Backus, S., author; Bartels, R., author; Macmillan Magazines Ltd., publisher (Colorado State University. Libraries, 2000)
When an intense laser pulse is focused into a gas, the light-atom interaction that occurs as atoms are ionized results in an extremely nonlinear optical process-the generation of high harmonics of the driving laser frequency. Harmonics that extend up to orders of about 300 have been reported, some corresponding to photon energies in excess of 500 eV. Because this technique is simple to implement and generates coherent, laser-like, soft X-ray beams, it is currently being developed for applications in science and technology; these include probing the dynamics in chemical and materials systems and imaging. Here we report that by carefully tailoring the shape of intense light pulses, we can control the interaction of light with an atom during ionization, improving the efficiency of X-ray generation by an order of magnitude. We demonstrate that it is possible to tune the spectral characteristics of the emitted radiation, and to steer the interaction between different orders of nonlinear processes.